Neural monitoring in thyroid surgery is here to stay - Zhang, Daqi (Gland Surg, 2020)
The iatrogenic injury of the recurrent laryngeal nerve (RLN), more clinically significant than those affecting the external branch of the superior laryngeal nerve (EBSLN), constitute one of the most feared perioperative complications of thyroid surgery and parathyroid glands, in terms of impact in clinical and economic-social costs. Moreover, these events rank among the leading reasons for medicolegal litigation of surgeons because of its attendant reduction in quality of life. The average incidence of RLN paralysis, permanent and temporary, after thyroidectomy is high and stands between 2.3% and 9.8% respectively. Given the elements described above, it is essential for the surgeon to adhere to a carefully standardized intraoperative technique that minimizes the possibility of RLN injuries. Intraoperative neuromonitoring (IONM) was introduced to reduce RLN injuries and for this reason, it achieved considerable success among endocrine surgeons. However, even today it is considered an adjunct device to the direct identification of the RLN. In this perspective, IONM of RLN constitutes an important aid, since it represents a reliable tool for the evaluation of functional neural integrity. Despite the ever-increasing diffusion of the IONM, prospective randomized studies are needed for further validation. The purpose of this work is to analyze scientific evidence to show that IONM in thyroid surgery is here to stay.